PELATIHAN ENGLISH SPEAKING DAN RETORIKA KOMUNIKASI MELALUI SPEECH DAN DEBATE BAGI SISWA DI SMK - Tomi Arianto; Afriana Afriana; Padrisan Jamba (PUAN INDONESIA, 2023)
SMK Bisa, SMK Hebat, and SMK Siap Kerja are the mottos that are often heard today as motto in SMK. Vocational High Schools are specifically directed to master a vocational from an early age so that Vocational High School graduates have specific abilities and can be competitive in the world of work. The current world of work also does not only master on hard skills, communication plays an important role for these students to support the vocational soft skill abilities. English as a medium of communication is also the most important role in the world of work. Moving on from the need to master communication with English media, the team of this community training took the initiative to go down to school to share their knowledge, especially in terms of English speaking. In communication skills are also needed to build an interesting atmosphere. Therefore, the rhetorical communication is needed as a way to build interesting atmosphere in speaking. Moving on from these problems the community team collaborated with language and social science experts implemented this activity by sharing knowledge toward vocational school in Batam. This training activity applied the community education with training and practice course technique. The training provided is oriented towards improving speaking and communication rhetoric skills through speech and debate methods. The results of this activity showed that students begin to enjoy practicing communication as speech speakers or debate speakers. Through this method, students felt more confident to speak English because they talk about contemporary topics and are close to the world of teenagers themselves.